Teledermatology Practice in a Department that Was Relocated Multiple Times during the COVID-19 Pandemic - Tatu AL (Clinical, Cosmetic and Investigational Dermatology, 2024)
Alin Laurentiu Tatu1– 3 1Dermatology Department, “Sfânta Cuvioasa Parascheva” Clinical Hospital of Infectious Diseases, Galati, Romania; 2Clinical Medical Department, Faculty of Medicine and Pharmacy, „Dunărea de Jos” University, Galati, Romania; 3Multidisciplinary Integrated Center of Dermatological Interface Research Center (MIC-DIR), “Dunărea de Jos” University, Galati, RomaniaCorrespondence: Alin Laurentiu Tatu, Tel +40 728267435, Email dralin_tatu@yahoo.comAbstract: The COVID pandemic inherently impacts clinical activity in Dermatological practices throughout all sectors. Under these circumstances, our service has implemented teledermatology in order to act both as a filter for reducing in-hospital admittance or face-to-face interactions, and as a straightforward solution to solve the issues faced by patients and family doctors within our area. Live consultations rely on the resident physician’s capacity to take a detailed patient history in the limited time allotted, while the subsequent case-discussion with the leading-physician has good didactic value. The establishment of a quality international collaboration through teledermatology would further facilitate a more accurate and faster diagnosis, even for patients traveling for business or tourism.Keywords: teledermatology, resident training, research tool, dermatology, COVID-19, residency training